2005
DOI: 10.1002/cbic.200500189
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Complex Mixtures of Novel Long‐Chain Quorum Sensing Signals in Free‐Living and Host‐Associated Marine Alphaproteobacteria

Abstract: More than 100 bacterial isolates from various marine habitats were screened for AHL production by using gfp reporter constructs based on the lasR system of Pseudomonas aeruginosa and the luxR system of Vibrio fischeri. Of the 67 Alphaproteobacteria tested, most of which belonged into the so-called Roseobacter clade, 39 induced fluorescence in either one or both sensor strains up to 103-fold compared to controls. Acylated homoserine lactones were identified by GC-MS analysis and shown to have chain lengths of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
216
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(227 citation statements)
references
References 49 publications
10
216
1
Order By: Relevance
“…This lack of complexity in QS signal profiles of the tested bacteria is different from the reports, in which a-and g-proteobacterial associates of sponges and marine dinoflagellates were shown to produce multiple AHLs, including signals with unusually long acyl side chains (Wagner-Dobler et al, 2005;Mohamed et al, 2008). Treatment with the AHL lactonase AiiA, significantly reduced appearance of the detectable TLC spots produced by the Marinobacter sp.…”
Section: Bioassay-guided Characterization Of Qs Signalscontrasting
confidence: 83%
See 1 more Smart Citation
“…This lack of complexity in QS signal profiles of the tested bacteria is different from the reports, in which a-and g-proteobacterial associates of sponges and marine dinoflagellates were shown to produce multiple AHLs, including signals with unusually long acyl side chains (Wagner-Dobler et al, 2005;Mohamed et al, 2008). Treatment with the AHL lactonase AiiA, significantly reduced appearance of the detectable TLC spots produced by the Marinobacter sp.…”
Section: Bioassay-guided Characterization Of Qs Signalscontrasting
confidence: 83%
“…The ability of marine prokaryotes and eukaryotes to excrete compounds that stimulate or inhibit QS reporters is now well documented (Pasmore and Costerton, 2003;Wagner-Dobler et al, 2005;Skindersoe et al, 2008;Teasdale et al, 2009;Kwan et al, 2010); however, ecological roles of these compounds and of the bacteria that produce them are less understood. Therefore, our subsequent experiments focused on testing the behaviors of the isolates in the dual-species microbial consortia consisting of the coral pathogen S. marcescens PDL100 and the isolate of interest.…”
Section: Effect On Swarming In Serratia Marcescensmentioning
confidence: 99%
“…Deletion of luxI 1 completely eliminates AHL production in D. shibae Previously it had been shown that D. shibae synthesizes C18en-HSL and C18dien-HSL in MB medium (Wagner-Dö bler et al, 2005. This was now also confirmed in the minimal medium used for microarray analyses by GC-MS (Supplementary Figure S2).…”
Section: Resultssupporting
confidence: 52%
“…shibae, like many other Proteobacteria, relies on acylated homoserine-lactones (AHLs) for cell-tocell communication. It produces C18en-HSL and C18dien-HSL with one and two unsaturations in the acyl side chain, respectively, which represent novel structures not described in any other bacterial species so far (Wagner-Dö bler et al, 2005). Genome analysis of D. shibae revealed the presence of three LuxI type AHL synthase genes (termed luxI 1 , luxI 2 , luxI 3 ).…”
Section: Introductionmentioning
confidence: 96%
“…S. meliloti produces a variety of longchain AHLs, including C18-, C16:1-, 3-oxo-C16:1-, 3-oxo-C14-, and C12-HSLs (8,9). AHLs with an acyl chain containing 14 or more carbons may be characteristic of α-proteobacteria, being identified in Rhodobacter capsulatus, Agrobacterium vitis, and several distant marine species as well (10)(11)(12). S. meliloti strains 1021 and 2011 have a single AHL-based QS system (Fig.…”
mentioning
confidence: 99%